The Case for Targeted Parenting Interventions with Reference to Intergenerational Transmission of Parenting: Qualitative Evidence from Three Studies of Marginalised Mothers' and Fathers' Participation in Parenting Programmes. Issue 3 (3rd July 2022) - Buston, Katie; O'Brien, Rosaleen; Maxwell, Karen
ABSTRACT: The idea that how you were parented is key to how you parent your own children is widely recognisable. It is present in popular cultural references, underpins much policy on families and parenting in the UK, and is supported by a substantive body of academic literature. We explore this concept of intergenerational transmission of parenting, understanding it as the context in which parenting interventions have been implemented. We draw on interview data from three Scottish samples of marginalised parents ( n  =   54) to explore how participants think their own parenting behaviours have been shaped by their experience of being parented and how they talk about participation in a parenting intervention in relation to this. We find that how these parents have been parented is salient in considering their own parenting behaviour, and is a key context for their engagement with the intervention. We make the case for parenting interventions targeted at marginalised parents, arguing that they are acceptable to, and useful for, these parents and may, potentially, be effective in breaking cycles of negative parenting. Policy-makers should not shy away from implementing targeted parenting programmes as part of endeavours to address negative parenting.